If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15/6m+7=14
We move all terms to the left:
15/6m+7-(14)=0
Domain of the equation: 6m!=0We add all the numbers together, and all the variables
m!=0/6
m!=0
m∈R
15/6m-7=0
We multiply all the terms by the denominator
-7*6m+15=0
Wy multiply elements
-42m+15=0
We move all terms containing m to the left, all other terms to the right
-42m=-15
m=-15/-42
m=5/14
| (9x+4)(3x-2)(3x-2)=180 | | (9x+4)(3x-2)=180 | | 4/7=m/28 | | F(x)=–x^2-7x-5 | | -14(d+3)=14 | | x=2/4(5x-4)=4x | | T=190+40w | | T=350+25w | | x^-3=118 | | 5x+19=45 | | r–17.1=−4.8* | | 900 =(n+2)180° | | 6(v+6)=72 | | 45=13x+19 | | 3x7-x=21 | | u/4-5=-1 | | 6(3k-4)=18k-24 | | 3p^2–40p+13=0 | | -14=1-5x | | -6(y+7)=-6 | | 4/15=1/4x | | 59=6x-5 | | 23x=9x | | 97-x=45 | | 19x+–9x=20 | | 3-5u=43 | | 11x=x^2+28 | | 4x-2=(x+2)^2-6 | | t+4=-t-4 | | 11x=x2+28 | | X+2x+1/x=66 | | 3-5z=-9+z |